EFFECT OF LOW CONCENTRATION ACETIC ACID ON CO2 CORROSION IN TURBULENT FLOW CONDITIONS - Che Ismail, Mokhtar (King Fahd Univeristy of Petroleum and Minerals, 2009)
CO2 corrosion is the main cause of failure in the upstream sector of the oil and gas industry. Interactions between some corrosive species, such as acetic acid (HAc), and operating conditions such as flow, could influence the CO2 corrosion mechanism and kinetics. The objective of this research was to study the mechanism and kinetics of CO2 corrosion in the presence of a low concentration of acetic acid in turbulent flow conditions at fixed pH and various temperatures. The electrochemical studies were based on linear polarization resistance (LPR) and potentiodynamic polarization. A Rotating Cylinder Electrode (RCE) apparatus was used to simulate turbulent conditions by correlating shear stress to represent pipe-flow condition. Based on the LPR results, CO2 corrosion rate was not significantly influenced by the presence of HAc below 40 ppm. An appreciable increase in corrosion rate up to 68% was only observed for HAc concentration of more than 40 ppm. HAc increases corrosion rate by increasing cathodic reaction through the direct reduction and dissociation reactions. It was also observed that corrosion rate increases with increasing temperature. This is due to the acceleration of anodic and cathodic reactions when temperature increases and the availability of more HAc species at higher temperature. Furthermore, an increase in the corrosion rate due to an increase in the rotational velocity was recorded in this study until 2000 rpm. Beyond this, not much effect of rotational velocity was observed. Flow effect is related to the transport of species towards and away from metal surfaces. Potentiodynamic polarization sweeps showed that the cathodic reaction slightly increases with the presence of a low concentration of HAc. There was no change in the mechanism of anodic reaction.